Implementasi Metode Tahfiz Dan Tahsin Di Rumah Tahfiz Khairunnas Ahmed Al-Ihsan Medan - Ahmad Faisal; Apriadi Amin; Rasyidin; Annisa Malihan; Rushaifah Mumtazah Lubis (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This research is motivated by the importance of mastering the Qur'an through tahsin (recitation improvement) and tahfiz (memorization) as an integral part of Islamic education. The purpose of this study is to implement and analyze the tahfiz and tahsin learning methods applied at Rumah Tahfiz Khairunnas Ahmed Al-Ihsan Medan, a special institution for female students. This study uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews with caregivers and female students, and documentation studies. The results show that the implementation of the tahfiz and tahsin learning methods at the institution is structured and intensive, combining the tasmi' (listening) method and direct tahsin coaching by teachers. The main methods applied are individual memorization (muraja'ah) deposits, additional independent memorization in a special zone, and tahsin classes to improve reading, tajweed rules, and makharijul huruf. A busy activity schedule integrated with daily worship supports the effectiveness of the memorization process. Key supporting factors include the guidance of dedicated female Islamic teachers, a supportive dormitory system, and fee waivers for female students. Challenges such as boredom and homesickness were successfully addressed through time management and scheduled communication. This research provides practical benefits in the form of an overview of an effective tahfiz-tahsin learning model in a female-only dormitory environment, which can serve as a reference for managers of similar institutions in optimizing Quran memorization programs.